Musical life of the Blood Indians - Witmer, Robert (Book collections on Project MUSE., 1982)
Revised version of author's master's thesis "The musical culture of the Blood Indians". Based on fieldwork done in 1968, this is an analytical description of the musical life of the Blood Indians of south-western Alberta